2021
DOI: 10.1101/2021.08.17.456641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-associated Senescent - T Cell Signaling Promotes Type 3 Immunity that Inhibits Regenerative Response

Abstract: Aging is associated with immunological changes that compromise response to infections and vaccines, exacerbate inflammatory diseases and could potentially mitigate tissue repair. Indeed, regenerative medicine strategies designed to promote tissue repair are now focusing on the immune system as a therapeutic target due to its role in response to tissue damage and regulation of tissue repair. However, age-related immune changes to the response to damage and the resulting impact on repair remains unknown. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Recent work has detailed the role of T lymphocytes in the response to a biological scaffold and found that aging induces senescence and increases IL-17-related signaling that impairs tissue repairs and therapeutic responses to biological scaffolds. 184 These studies raise the importance of age-specific innate and adaptive immune responses to biomaterials, including context-specific macrophage responses, and their implication for limiting the foreign body response.…”
Section: Challenges For Targeting the Fbr In Humansmentioning
confidence: 99%
“…Recent work has detailed the role of T lymphocytes in the response to a biological scaffold and found that aging induces senescence and increases IL-17-related signaling that impairs tissue repairs and therapeutic responses to biological scaffolds. 184 These studies raise the importance of age-specific innate and adaptive immune responses to biomaterials, including context-specific macrophage responses, and their implication for limiting the foreign body response.…”
Section: Challenges For Targeting the Fbr In Humansmentioning
confidence: 99%